Prevention of nosocomial transmission of extensively drug-resistant tuberculosis in rural South African district hospitals: an epidemiological modelling study. - Basu, Sanjay; Andrews, Jason R; Poolman, Eric M; Gandhi, Neel R; Shah, N Sarita; Moll, Anthony; Moodley, Prashini; Galvani, Alison P; Friedland, Gerald H (Lancet, 2007)
Extensively drug-resistant (XDR) tuberculosis has spread among hospitalised patients in South Africa, but the epidemic-level effect of hospital-based infection control strategies remains unknown. We modelled the plausible effect of rapidly available infection control strategies on the overall course of the XDR tuberculosis epidemic in a rural area of South Africa.
Keywords: Cross Infection; Hospitals, District; Humans; Models, Theoretical; Rural Health; South Africa; Tuberculosis, Multidrug-Resistant